PERLINDUNGAN HUKUM BAGI ANAK DARI TINDAK PIDANA ABORSI - Siregar, Rospita Adelina; situmorang, Isaulina (MAGISTRA Law Review, 2024)
As a result of information disclosure, the impact of changing a person's lifestyle can be seen in all age groups. It is felt to be very disturbing when a minor becomes pregnant and chooses to have an abortion because of her mental and physical unpreparedness. This openness of information and technology can change the behaviour of children, aged 11-15 years, so that they are very easily influenced by the environment in which they live, including their desire to have sex. How to prevent the crime of abortion by minors is the focus of research carried out in a normative juridical manner, using a literature study approach and presented using analytical descriptives. Allowing abortion at a child's age certainly does not negate the provisions of article 9 paragraph (1) of Law Number 39 of 1999 concerning Human Rights which emphasizes the right to life of every person. Then article 53 of Law number 39 of 1999 concerning Human Rights which states that every child from the womb has the right to live. On the other hand, Positive Law in Indonesia regulates in article 1 point 2 of Law number 35 of 2014 concerning amendments to Law Number 23 of 2002 concerning Child Protection, stating that "child protection is all activities to guarantee and protect children and their rights in order to live, grow, develop. So all parties should help educate and monitor the development of children as a whole so that they do not have sex before their time, because there are articles that prohibit abortion, Articles 299, 346, 347, 348, and 349. Abortion is permitted if a medical emergency occurs in pregnant women